Microorganismos (hongos y bacterias “género Bacillus”) asociados a la rizosfera del cacao en diferentes sistemas de producción en el cantón Portoviejo - Mendoza Rodríguez, María Daniela (2021)
In the present research work, it was possible to determine the fungi and bacteria of the Bacillus genus associated with the cacao rhizosphere in different production systems in the Portoviejo canton, which were: Monoculture, cacao with citrus fruits and cacao with timber at both times of the year , dry and rainy season. In this way, it was possible to know which were the most influential fungal families in these soils. A total of eight groups of fungi were identified: 1) Cladosporium, 2) Penicillium, 3) Trichoderma harzianum, 4) Aspergillus, 5) Paecilomyces, 6) Beauveria, 7) Fusarium solani and 8) Bipolaris tetramera; while, in the case of bacteria, only one species of the genus Bacillus was identified. In the dry season six species were found: Cladosporium, Penicillium and Trichoderma harzianum, Aspergillus, Cladosporium, Paecilomyces. While in the rainy season seven were found: Beauveria, Cladosporium, Paecilomyces, Penicillium, Fusarium solani, Aspergillus, Bipolaris tetramera. Low biodiversity indices: H Shannon = 0.92–1.03 for the dry season and 0.88–1.56 for the rainy season; and H Simpson = 0.40–0.45 in dry season and 0.22–0.48 in rainy season; although in the latter case 0.22 is closer to 0 indicating greater biodiversity of the habitat. The rainy season is more optimal for the abundance of species; registering a total of 7137 vs 5951 colonies of bacteria in the dry season and 117 vs 60 isolation of fungal colonies, respectively. For this, sampling points and the collection of samples were established following the processes of the methodology given by Alvis, (2009).